Flow cytometry in medical research and clinical applications - Lao-araya, Mongkol (Biomedical Sciences and Clinical Medicine, 2014)
Flow cytometry is a technique used to evaluate multiple parameters of individual cell by measuring the light wavelength they scatter or emit as they stream individually through a light source. The flow cytometer has been developed since the 1970’s and rapidly became an essential instrument for medical sciences especially in hematology and immunology. This technique has evolved together with technology in monoclonal antibody and the fluorescent molecules, leading to many clinical applications and transforming our understanding of immunology. Presently, almost 200,000 research articles in Medline referencing flow cytometry have been published. This review focuses primarily on basic background information for evaluation of flow cytometry data and its applications in research and clinical practice.